Long term responses and adaptive strategies of Pistacia lentiscus under moderate and severe deficit irrigation and salinity: Osmotic and elastic adjustment, growth, ion uptake and photosynthetic activity - Álvarez, S.; Rodríguez, P.; Broetto, F. [UNESP]; Sánchez-Blanco, M. J. (Elsevier, 2018)
Pistacia lentiscus is a wild species that grows widely in the Mediterranean area. However, despite it appearing to be particularly resistant to some stressful conditions, drought and salinity may alter its physiological and morphological behavior. While the responses of P. lentiscus to both stresses have been partially studied, its avoidance and tolerant mechanisms are poorly understood. In particular, changes in leaf tissue cell wall and the photosynthetic activity during a prolonged water deficit and salinity are unknown. Nursery grown plants were subjected to four irrigation treatments lasting eleven months: control (1 dS m−1, 100% water holding capacity), two deficit treatments (moderate and severe water deficit, corresponding to 60 and 40% of control) and saline treatment (4 dS m−1, same amount of water supplied as control). Biomass accumulation was affected more by deficit irrigation than by salinity. Salt tolerance in P. lentiscus was associated with the restricted uptake of Cl− and its storage in roots. However, the cumulative effect of irrigating with saline water involved an over-accumulation of Na+ and Cl− in leaves, which probably contributed to the pronounced decrease in photosynthesis, confirming the importance of the length of exposure of the plants to salt stress. Plants under saline or severe deficit irrigation exhibited slight dehydration throughout the experiment, as indicated by the lower leaf water potential and relative water content, due to the low availability of substrate water (osmotic effect). The response of plants to severe water stress, which resulted in stomatal closure and a decrease in net photosynthesis rate, involved a marked decrease in plant height and growth, especially in the first months of the experiment, after which a slight acclimation may have occurred in these plants. Under moderate water stress, most of these responses were mitigated. Salinity induced active osmotic adjustment and decreased leaf tissue elasticity. Due to its tolerance of water stress and salinity, P. lentiscus is a suitable ornamental species for gardening in arid and saline area.
Keywords: Elastic modulus; Gas exchange; Mediterranean shrub; Osmotic adjustment; Pressure-volume curves; Water relations